China–Africa Higher Education Engagement: A Win–Win Situation? - Mohamedbhai, Goolam (International Higher Education, 2020)
China’s economic activities in Africa have been accompanied by several initiatives to promote African higher education development. This forms part of China’s soft power strategy. But does this lead to a win–win situation for Africa and China? And what does the future hold for Africa as a result of China’s increasing engagement?